2012
DOI: 10.1371/journal.pone.0033967
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Multiple Locus Variable Number of Tandem Repeat Analysis (MLVA) of Staphylococcus aureus from Human, Animal and Food Sources

Abstract: Staphylococcus aureus is a major human pathogen, a relevant pathogen in veterinary medicine, and a major cause of food poisoning. Epidemiological investigation tools are needed to establish surveillance of S. aureus strains in humans, animals and food. In this study, we investigated 145 S. aureus isolates recovered from various animal species, disease conditions, food products and food poisoning events. Multiple Locus Variable Number of Tandem Repeat (VNTR) analysis (MLVA), known to be highly efficient for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 53 publications
(92 reference statements)
2
48
0
3
Order By: Relevance
“…Besides, the MLVA-10 scheme could easily be automated using fluorescent primers and a single multiplex PCR (31). Capillary electrophoresis would allow automatic size measurement of the PCR products and thus increase the accuracy of repeat number determination, as described for other bacterial species (31)(32)(33). Furthermore, some potentially informative VNTR markers that were ruled out from the present scheme due to short repeats (Ͻ15 bp) could be included to constitute a second panel with high discriminatory power, as has been proposed for other bacteria (34).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the MLVA-10 scheme could easily be automated using fluorescent primers and a single multiplex PCR (31). Capillary electrophoresis would allow automatic size measurement of the PCR products and thus increase the accuracy of repeat number determination, as described for other bacterial species (31)(32)(33). Furthermore, some potentially informative VNTR markers that were ruled out from the present scheme due to short repeats (Ͻ15 bp) could be included to constitute a second panel with high discriminatory power, as has been proposed for other bacteria (34).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that livestock associated MRSA originally were methicillin-susceptible commensal strains in pigs, whose spread was facilitated by the abundant use of antibiotics in pig and cattle farming (Voss et al, 2005). S. aureus is a major human pathogen, a relevant pathogen in veterinary medicine, and a major cause of food poisoning (Sobral et al, 2012). A joint ECDC/EFSA/EMA (2009) scientific report demonstrated that pigs are a major reservoir of a new emerging type of MRSA and concluded that the extensive use of antibiotics for prevention of disease appears to be an important risk factor for the spread of MRSA.…”
Section: Role Of Food In Disease Transmission: Resistance and Diseasementioning
confidence: 99%
“…Thus, epidemiological approaches monitoring S. aureus strains need to be established. Therefore, Sobral et al [23] developed an MLVA-CE method exploiting 16 VNTR loci amplified in two multiplex PCRs with analyzed PCR products using CE to genotype human S. aureus isolates in a highly efficient and discriminating manner. Du et al [24] developed and evaluated an improved multilocus VNTR fingerprinting using CGE for detection (CGE-MLVF), which replaced AGE (traditional MLVF) with CGE.…”
Section: Detecting and Diagnosing Bacteriamentioning
confidence: 99%